A Comparison of Generic Skills and Emotional Intelligence in Accounting Education - Daff, L.; De Lange, Paul; Jackling, B. (American Accounting Association, 2012)
Embedding generic skills such as communication and teamwork in the accounting curriculum continues to attract attention from stakeholders. In parallel, the business world and more recently some faculty, have recognized and explored the need to incorporate emotional intelligence (EI) in the curriculum. EI is viewed as a desirable quality as it allows accountants to excel in strategic decision making, teamwork, leadership, and client relations. We contend that in the quest to find the best employees, employers have focused on EI, whereas accounting faculty have placed less emphasis on EI skill development and a greater emphasis on generic skills. This paper addresses the need for accountants to have a combination of EI and generic skills. The commonalities and differences between an EI framework and a generic skills framework are identified when the two are juxtaposed. This provides guidance for faculty seeking to develop highly skilled graduates via the development of a range of curriculum resources designed to enhance EI.